2022
DOI: 10.1007/s10488-022-01205-2
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Evidence-Based Practice of Professionals Working with Children and Adolescents with Autism Spectrum Disorder in Bangladesh

Abstract: Like in many lower-middle-income countries (LMIC), progress in implementing evidence-based practices (EBPs) for children with autism spectrum disorder (ASD) has been slow in Bangladesh. This cross-sectional study examined professionals’ attitudes towards evidence-based practice (EBP) for children and adolescents with ASD and explored how providers’ demographic factors are related to attitudes to and adoption of EBPs in Bangladesh. The sample consisted of 150 mental health professionals and special teachers fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 91 publications
0
4
1
Order By: Relevance
“…Nevertheless, this study disagreed with the study conducted by Pervin and Hagmayer (2022) in Bangladesh. The findings indicated that professionals have favorable attitudes towards EBP.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, this study disagreed with the study conducted by Pervin and Hagmayer (2022) in Bangladesh. The findings indicated that professionals have favorable attitudes towards EBP.…”
Section: Discussioncontrasting
confidence: 99%
“…The results support other studies that have shown the balance, appeal, and divergence subscales of the EBPAS-36 to have marginally acceptable reliability. 30,31,35 A nal study aim was to examine correlates of provider attitudes toward EBP. Female gender was associated with more positive attitudes, a nding that has emerged in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…30 Other studies also have found that the appeal, balance, divergence, and t subscales have questionable internal consistency. 31,35 Additionally, multiple versions of the EBPAS have been tested in various samples of mental health providers, but few of these studies have explicitly focused on professionals who are trained in an evidence-based intervention.…”
Section: Rationale For Further Studymentioning
confidence: 99%
“…HAC is designed to suit the needs of parents in South Asia, with adaptations designed in co-production with clinicians, researchers and parents of autistic children to ensure suitability and cultural appropriateness. 10 The Helping your Anxious Child programme Helping your Anxious Child was developed through collaborations via the North East England South Asia Mental health Alliance (NEESAMA; www.NEESAMA.org). NEESAMA seeks to bring together international partners in the UK and South East Asia to improve research, training and clinical service delivery within mental health services.…”
Section: Special Papermentioning
confidence: 99%
“…HAC is designed to suit the needs of parents in South Asia, with adaptations designed in co-production with clinicians, researchers and parents of autistic children to ensure suitability and cultural appropriateness. 10 …”
mentioning
confidence: 99%